Oxytocin and potential benefits for obesity treatment. Issue 5 (October 2017) - Olszewski, Pawel K.; Klockars, Anica; Levine, Allen S.
Abstract : Purpose of review: Laboratory animal experiments have consistently shown that oxytocin causes early termination of food intake, thereby promoting a decrease in body weight in a long term. Recent studies have also assessed some of oxytocin's effects on appetite and energy balance in humans. The present study examines the findings of the key basic research and of the few clinical studies published thus far in the context of potential benefits and challenges stemming from the use of oxytocin in obese patients. Recent findings: Basic research indicates the involvement of oxytocin in satiety, processing, in reducing a drive to eat for pleasure and because of psychosocial factors. Although the results of clinical studies are very scarce, they suggest that oxytocin administered intranasally in humans decreases energy-induced and reward-induced eating, supports cognitive control of food choices, and improves glucose homeostasis, and its effectiveness may be BMI dependent. Summary: Despite the wealth of basic research showing broad anorexigenic effects of oxytocin, clinical studies on oxytocin's therapeutic potential in obesity, are still in their infancy. Future implementation of oxytocin-based pharmacological strategies in controlling energy balance will likely depend on our ability to integrate diverse behavioral and metabolic effects of oxytocin in obesity treatment regimens.